2015
DOI: 10.1111/ggi.12486
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia is an independent risk factor of dysphagia in hospitalized older people

Abstract: Sarcopenia was an independent risk factor for dysphagia among older individuals. However, further studies are required to define causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
146
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 18 publications
6
146
0
3
Order By: Relevance
“…Unlike some previous reports on smaller patient populations [1, 23], but similar to another recent publication [22], dysphagic patients were on average 5 years older ( p < 0.001) in our study, indicating age as a clear risk factor for swallowing impairment after stroke. This may be explained by a limited functional reserve and sarcopenia in the aged population [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Unlike some previous reports on smaller patient populations [1, 23], but similar to another recent publication [22], dysphagic patients were on average 5 years older ( p < 0.001) in our study, indicating age as a clear risk factor for swallowing impairment after stroke. This may be explained by a limited functional reserve and sarcopenia in the aged population [24, 25]. …”
Section: Discussionmentioning
confidence: 99%
“…Upper limits of tongue capability were investigated by Alsanei et al [23]: maximum isometric tongue pressure (MITP) was well-correlated to the maximum hardness of mashed potato or vege-gel which could be crushed by the tongue alone. Decreased MITP resulting from sarcopenia was identified as an independent risk factor for dysphagia [24], [25*] so there is a potential risk of inadequate nutritional intake worsening swallowing function, but the vicious cycle could be halted by nutritional supplements and effective dysphagia management.…”
Section: Research In Swallowing and Rheologymentioning
confidence: 99%
“…Furthermore, T‐EAT‐10 scores were analyzed by dysphagia status. In the normal group the T‐EAT‐10 score median (IQR) was 2, in the penetration‐positive group the median (IQR) was 2, and in the aspiration‐positive group the median was 11 . T‐EAT‐10 scores were highest in the aspiration‐positive group compared with others ( P = 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Elderly subjects with both sarcopenia and dysphagia may have not only disease‐related dysphagia but also sarcopenic dysphagia. The prevalence of swallowing disorders in older individuals ranges from 13% to 38%, and a few studies reported the prevalence of sarcopenic dysphagia to be between 30% and 42.2% . Signs and symptoms associated with dysphagia may include odynophagia, drooling, hoarseness, regurgitation, heartburn, coughing or gagging, and frequent pulmonary infections.…”
Section: Introductionmentioning
confidence: 99%